Evaluation Of Thinking Skilss Learning At Pesantren Kuliyyatul Mu’allimin Al-Islamiyah (KMI) - Yuliana; Aan Hasanah; Mohamad Erihadiana; Bambang Samsul Arifin; Didi Mulyadi (International Journal of Educational Research & Social Sciences, 2021)
This article discusses the evaluation of learning to form thinking skills in one of the pesantren that implements the Kuliyyatul Mu'allimin Al-Islamiyah (KMI) program. This study aims to identify learning evaluations that train students' thinking skills at Pondok Pesantren (PP)  Darussalam Kunir, Subang. The approach used in this study is qualitative with descriptive methods to identify, describe, and analyze information needs regarding the evaluation of learning in the pesantren being studied. Data collection was done by interview, observation, and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that the evaluation of learning at PP Darussalam Kunir Subang in the form of the Tahriri Exam (Written Examination) and the Syafahi Exam (Oral Examination) tended to be dominated by questions in the realm of low-level thinking. The conclusion of this study is that efforts to form students' thinking skills in pesantren require an evaluation of learning by paying attention to indicators that can direct students' skills in cognitive aspects in order to be able to answer questions in the higher-order thinking domain with more composition than in the lower-order thinking domain.